The early John Maynard Keynes: An intellectualist becomes disappointed - Soroush Marouzi (Duke University, Center for the History of Political Economy (CHOPE), 2023)
John Maynard Keynes's philosophical outlook evolved from the outbreak of the Great War in 1914 up until the publication of his A Treatise on Probability in 1921. The evolution of Keynes's philosophical perspectives was closely intertwined with the debates surrounding Cambridge rationalism within the Bloomsbury group - a prominent intellectual circle that counted Keynes among its members. These debates were spurred by the outbreak of the Great War and the presentation of Clive Bell's aesthetic theory in 1914. The Bloomsbury group of the early twentieth century adopted a specific variant of Cambridge rationalism that advanced three theses. First, the ontological thesis that there is a spiritual world that stands above material conditions. Second, the epistemological thesis that the domain of reason is exhausted by human intellect. Third, the psychological thesis that human nature is reasonable. Although Keynes remained consistent in his adherence to the ontological thesis of Cambridge rationalism, his view of the epistemological and psychological theses of that rationalism underwent modifications in the second half of the 1910s. Keynes's complex treatment of Cambridge rationalism left its mark on his account of the ontological status of probability relations, his formulation of rationality, and his conception of the psychology of probabilistic reasoning.
Keywords: 330